2014
DOI: 10.1111/jrh.12063
|View full text |Cite
|
Sign up to set email alerts
|

Medical Mistrust, Perceived Discrimination, and Satisfaction With Health Care Among Young‐Adult Rural Latinos

Abstract: Medical mistrust and perceived discrimination were significant contributors to lower satisfaction with health care among young-adult Latinos living in rural Oregon. Health care reform implementation, currently under way, provides a unique opportunity for developing evaluation systems and interventions toward monitoring and reducing rural Latino health care disparities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
64
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 35 publications
3
64
0
Order By: Relevance
“…For example, we were unable to adjust for other measures of socioeconomic position (due to data quality issues in collected data) or measures of social desirability (as these were not included in the original NZHS data collection). In addition, we could not examine measures of trust in medical care or providers in our models, which is often examined as a mediator in the association between racial discrimination and satisfaction in healthcare 36–38 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, we were unable to adjust for other measures of socioeconomic position (due to data quality issues in collected data) or measures of social desirability (as these were not included in the original NZHS data collection). In addition, we could not examine measures of trust in medical care or providers in our models, which is often examined as a mediator in the association between racial discrimination and satisfaction in healthcare 36–38 …”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with international research demonstrating a link between experience of racism and higher unmet need, 16,29,34,35 and lower satisfaction. 14,34,36,37 These studies have demonstrated links between racism within the health setting 14,34,35,37,38 and other forms of racism 16,29,36,38 with healthcare measures. Most of these studies were undertaken in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Although some discussions of incidents where members felt discriminated against occurred during board meetings, discussion of discrimination and marginalization during the interviews was notably more prominent. In quantitative studies, perceived discrimination in health care among Latinos has been associated with lower health care satisfaction and reports of worse doctor–patient communication (López-Cevallos, Harvey, & Warren, 2014; Perez, Sribney, & Rodríguez, 2009; Shavers et al, 2012). Parental report of a medical home in national surveys often depends on positive responses to questions that deal with satisfaction with care and doctor–patient communication.…”
Section: Discussionmentioning
confidence: 99%
“…Perceived discrimination may result in more negative responses to these types of questions but has yet to be explored as a contributor to the lower medical home prevalence for Latino children. Prior quantitative research focused on experiences of discrimination have found foreign-born, Spanish-speaking Latinos are less likely to report discrimination in health care than nonimmigrants or English speakers (López-Cevallos et al, 2014; Perez et al, 2009; Shavers et al, 2012). The poignant and prevalent discrimination described by board members contrasts with these quantitative findings.…”
Section: Discussionmentioning
confidence: 99%
“…In one study, up to 40% of foreign-born older Latinos were found to have undiagnosed dementia for at least 3 years (2). Because rural dwelling Latinos are a rapidly growing sub population, and yet have some of the poorest access to, and utilization of healthcare services, culturally-acceptable and easily administered interventions designed for this specific population hold potential to have a wide impact(3). …”
Section: Introductionmentioning
confidence: 99%